(untitled) (KULT_online, 2010)
Alexandra Ganser investigates Roads of Her Own – Gendered Space and Mobility in American Women’s Road Narratives, 1970-2000 against the backdrop of the spatial turn, paying special attention to feminist cultural geography. As Ganser’s point of departure, ‘the road’ functions as mythical and highly gendered space for male freedom. The author then asks to what extent women’s road narratives use or rewrite the masculinely dominated conventions of the road genre. To this end, she employs a ‘transdifferent’ analytical approach. That is, rather than zooming in on gender issues, she relates them constantly to other categories of identities and cultural difference, such as ethnicity, age or class.